Acute effects of foam-rolling on jump height and soft tissue stiffness - Baumgart, C.; Kühnemann, M.; Hoppe, M. W.; Freiwald, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Foam-rolling is frequently used during warm-up and regeneration procedures for self-myofascial release [1]. However, the acute effects on performance and potentially underlying soft tissue properties are not fully understood. Therefore, the study aimed to evaluate the acute effects of foam-rolling on jump height and soft tissue stiffness of the lower extremities. Twenty male active subjects (26.9 ± 2.6 years, 181.6 ± 6.8 cm, 80.4 ± 9.1 kg) were randomized to execute the following three interventions: 2x30 repetitions of foam-rolling (FR) on the thigh and calf (BLACKROLL, Bottighofen CH), 10 min of ergometer cycling (EC), and controls (CO). Before as well as 0, 15, and 30 min after each intervention, three countermovement jumps were performed on a force plate (Kistler 9287BA, Winterthur CH). Soft tissue stiffness was measured on two points (M. rectus fem., M. gastrocnemius med.) of both legs by myomechanography (MyotonPRO AS, Tallinn EST). Data were analyzed using a two-way repeated measures ANOVA (time x intervention) as well as one-way repeated measures ANOVA with post-hoc Bonferroni correction. Pearson correlation coefficients were used to investigate relationships between changes in the jump height and stiffness. A significant main interaction (time x intervention) was found in jump height (p<.001, eta²=.81) and stiffness of M. rectus fem. (left: p=.002, eta²=.74, right: p=.008, eta²=.67). Thereby, jump height increased only after EC (34.8±3 vs. 36.4±3 cm, p=.001) and decreased thereafter as in FR and CO. Stiffness of M. rectus fem. decreased after FR (left: 266±24 vs. 260±27 N/m, p=.01; right: 268±32 vs. 260±33 N/m, p=.004) and return to pre-values afterwards. However, the increase in stiffness of M. rectus fem. after EC was not significant (left: 265±28 vs. 270±31 N/m, p=.17; right: 270±33 vs. 275±34 N/m, p=.12). The Pearson correlation coefficient between the changes in jump height and stiffness of M. rectus fem. after all interventions was .40 (p=.002). Soft tissues properties were altered after foam-rolling. In contrast to a traditional warm-up on a cycling ergometer, the jump height did not increase and the soft tissue stiffness of the thigh decreased after foam-rolling. Therefore, the isolated use of a foam-roller as a warm-up procedure before explosive activities seems to be questionable. Future studies have to show if the decrease of the stiffness is caused by fascial, muscular, and/or other soft tissues.